Analisis Karakter Religius Pada Anak Usia 5-6 Tahun di Desa Gaseu Aceh Barat - Fitri Yani; Hayati, Zikra; Munawwarah (Asghar: Jurnal of Children Studies, 2024)
Children's religious character can be analyzed by mentioning the name of their God and the religion they embrace, understanding that living things and their surroundings are God's creations and children can explain the existence of symbols that reflect their religious practices such as religious holidays, places of worship and others. The role of parents is very important in shaping the religious character of children aged 5-6 years. This study aims to determine the religious character of children aged 5-6 years in Gaseu Village, West Aceh. This study uses descriptive qualitative research with data collection techniques through observation, interviews and documentation. The subjects of this study were 3 children in Gaseu Village aged 5-6 years, and 3 parents of children studied in Gaseu Village, West Aceh. The results of the study showed that one subject experienced development and two other subjects had not experienced development in mentioning the name of their God and the religion they embraced, in the second indicator one subject experienced development and two other subjects had not experienced development in knowing that living things and the surroundings are God's creations, while in the third indicator two subjects experienced development and one other subject had not experienced development in explaining the existence of symbols that reflect their religious practices.